ACTIN DEPOLYMERIZING FACTOR4 Regulates Actin Dynamics during Innate Immune Signaling in Arabidopsis . Issue 1 (24th January 2014) - Henty-Ridilla, Jessica L.; Li, Jiejie; Day, Brad; Staiger, Christopher J.
Abstract : Disruption of the host-cell actin cytoskeleton promotes the susceptibility of plants to diverse microbes. However, the signaling cascades and regulatory proteins linking the perception of microbes to cytoskeletal remodeling remain largely uncharacterized. This study implicates a key actin binding protein, ACTIN DEPOLYMERIZING FACTOR4, in plant innate immune signaling. Abstract: Conserved microbe-associated molecular patterns (MAMPs ) are sensed by pattern recognition receptors (PRRs ) on cells of plants and animals. MAMP perception typically triggers rearrangements to actin cytoskeletal arrays during innate immune signaling. However, the signaling cascades linking PRR activation by MAMPs to cytoskeleton remodeling are not well characterized. Here, we developed a system to dissect, at high spatial and temporal resolution, the regulation of actin dynamics during innate immune signaling in plant cells. Within minutes of MAMP perception, we detected changes to single actin filament turnover in epidermal cells treated with bacterial and fungal MAMPs . These MAMP -induced alterations phenocopied an ACTIN DEPOLYMERIZING FACTOR4 ( ADF4 ) knockout mutant. Moreover, actin arrays in the adf4 mutant were unresponsive to a bacterial MAMP, elf26, but responded normally to the fungal MAMP, chitin. Together, our data provide strong genetic and cytological evidence for the inhibition of ADF activity regulating actin remodeling during innate immune signaling. This work is the first to directly link an ADF/cofilin to the cytoskeletal rearrangements elicited directly after pathogen perception in plant or mammalian cells.